(untitled) - Morrison, Mike; Mike Morrison; Joline Morrison (New York, 2002)
Learn to build and deploy dynamic Web applications that interact with a powerful database. Readers with two prior programming courses will learn to get the most out of Visual Studio .NET, Oracle9i and Microsoft Access 2002. Expanded from 9 to 11 chapters, this text also provides background on subjects such as HTML, client-side scripting and relational databases. Readers set up their own personal Web site using a Microsoft Web Server to illustrate Web site creation and administration principles. Multiple running case studies put the lessons being learned into real world context
Keywords: Library Web sites; Library Web sites